Preparation method of copper oxide-carbon nitride nanotube composite particle with core-shell structure, composite particle and application

By forming core-shell structure copper oxide-carbon nitride composite particles on carbon nitride nanotubes, the problem of poor performance of carbon nitride in the field of photocatalytics is solved, and the photocatalytic performance is significantly improved, especially in photolysis of water Catalytic efficiency in hydrogen production.

CN119318981APending Publication Date: 2025-01-17JIANGYIN JIANGHUA MICROELECTRONICS MATERIAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411438054.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing application of carbon nitride in the field of photocatalysis is limited by its disadvantages such as its large bandwidth, easy recombination of electron holes and small specific surface area, resulting in poor photocatalytic performance.

Method used

The carbon nitride nanotubes were prepared by water-induced phase transformation formation method, and the copper salt was calcined in a reducing atmosphere to form core-shell structure copper oxide-carbon nitride nanotube composite particles, adjust the electronic structure and energy band position, and improve electrical performance. and photocatalytic capacity.

Benefits of technology

By forming a Z-type energy band structure, the charge carrier transfer and photoreduction capabilities are improved, the morphological control difficulty of composite catalysts is reduced, and the photocatalytic performance is significantly improved, especially the catalytic hydrogen production rate in photohydrogen production by photolysis and hydrogen production .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318981A_ABST
    Figure CN119318981A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a copper oxide-carbon nitride nanotube composite particle with a core-shell structure. The preparation method comprises the following steps: S1, preparing a carbon nitride nanotube by a water-induced phase transformation forming method; s2, dispersing a predetermined amount of carbon nitride nanotubes in deionized water, and uniformly mixing to obtain a carbon nitride dispersion liquid; s3, soluble copper salt is added into the carbon nitride dispersion liquid, stirring and mixing are conducted, drying and grinding are conducted, and mixed powder is obtained; and S4, calcining the mixed powder in a reducing atmosphere, and grinding to obtain the core-shell structure copper oxide-carbon nitride nanotube composite particles. The core-shell structure of the copper oxide-carbon nitride nanotube composite particle can adjust the electronic structure and improve the electrical properties of the material; cu2O nuclear energy is introduced, so that the energy band position of the core-shell structure nano-particles is raised, a Z-type energy band structure is formed, charge carrier transfer is accelerated, and the photo-reduction capacity is improved. The invention further discloses the copper oxide-carbon nitride nanotube composite particle with the core-shell structure and application of the copper oxide-carbon nitride nanotube composite particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalyst carbon nitride, and in particular to a preparation method of core-shell structure copper oxide-carbon nitride nanotube composite particles, the composite particles and applications. Background Art

[0002] Carbon nitride is a low-cost, chemically stable, narrow bandgap (λ> 420 nm), and highly responsive to visible light. It is widely used in photocatalytic fields such as photocatalytic water splitting to produce hydrogen, degradation of organic pollutants, and reduction of carbon dioxide. 3 N 4 There are some disadvantages, such as large bandgap (2.7 eV), easy recombination of electrons and holes, and small specific surface area, which greatly restrict its application in the field of photocatalysis. The improvement methods include structural regulation, doping modification and heterojunction design.

[0003] Improved process is closely related to the results of carbon nitride structure regulation. CN112774718A discloses a composite catalyst of cuprous oxide and tubular graphite-like carbon nitride. The tubular graphite-like carbon nitride is used as a raw material, and the tubular graphite-like carbon nitride is dispersed in a copper salt solution to obtain a suspension; then the suspension is heated to 50-70°C, and a strong alkali solution is slowly dripped under stirring conditions. After the strong alkali solution is dripped, the stirring reaction is continued for 10-20 minutes, and then a glucose solution is quickly poured in at once, and aged at 50-65°C for 2.5-3 hours to obtain the result. The feeding method using glucose as a reducing agent will significantly affect the particle size of cuprous oxide, affect the distribution of cuprous oxide inside and outside the tubular graphite-like carbon nitride tube, and increase the difficulty of morphology control of the composite catalyst. Summary of the invention

[0004] One of the purposes of the present invention is to overcome the defects existing in the prior art and provide a method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles, using carbon nitride nanotubes as raw materials and preparing core-shell structured carbon nitride nanotubes by calcining in a reducing atmosphere, thereby reducing the difficulty of controlling the morphology of the composite catalyst.

[0005] In order to achieve the above technical effects, the technical solution of the present invention is: a method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles, comprising the following steps: S1: Preparation of carbon nitride nanotubes by water-induced phase transition formation; S2: dispersing a predetermined amount of carbon nitride nanotubes in deionized water and mixing to obtain a carbon nitride dispersion; S3: adding soluble copper salt to the carbon nitride dispersion, stirring and mixing, drying and grinding to obtain a mixed powder; S4: calcining the mixed powder in a reducing atmosphere, and grinding to obtain core-shell structured copper oxide-carbon nitride nanotube composite particles.

[0006] A preferred technical solution is that the mass volume concentration of the carbon nitride nanotubes and deionized water is 1 to 9 mg / mL.

[0007] The preferred technical solution is that the soluble copper salt is copper nitrate, and the mass ratio of the carbon nitride nanotubes to copper nitrate is (1.74-4.14):1. The mass ratio of the carbon nitride nanotubes to copper nitrate can be selected as 1.74:1, 2:1, 2.25:1, 2.5:1, 2.75:1, 3:1, 3.25:1, 3.5:1, 3.75:1, 4:1, 4.14:1 or an interval with any two points as the maximum and minimum values, further (2-3.8):1, and further (2.5-3.1):1.

[0008] The preferred technical solution is that the reducing atmosphere contains hydrogen and inert gas, and the volume percentage of hydrogen in the reducing atmosphere is 2% to 20%, further 2% to 10%, and further 5%. If the volume percentage of hydrogen in the reducing atmosphere is too large, the copper oxide will be reduced to copper oxide excessively, and there will be no obvious core-shell structure nanoparticles on the surface of the carbon nitride nanotubes.

[0009] The preferred technical solution is that the calcination temperature of S4 is 390-440°C, and the calcination temperature can be selected as 390°C, 395°C, 400°C, 405°C, 410°C, 415°C, 420°C, 430°C, 440°C or an interval with any two points as the maximum and minimum values, further 390-425°C, and further 390-415°C.

[0010] The preferred technical solution is that the calcination time of S4 is 0.5 to 5 hours. Based on the preferred calcination temperature, the calcination time can be selected as 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h point values ​​or an interval with any two point values ​​as the maximum and minimum values, further 1 to 4 hours, and further 1.6 to 3.5 hours.

[0011] A preferred technical solution is that the drying temperature in S3 is 65-90°C, further 75-90°C, and further 80°C.

[0012] The preferred technical solution is that the diameter of the carbon nitride nanotube is 80-110 nm, and the length is 0.9-1.2 μm. The diameter of the carbon nitride nanotube is further 85-107 nm, and further 90-105 nm; the length of the carbon nitride nanotube is 0.93-1.15 μm, and further 0.95-1.1 μm.

[0013] The second object of the present invention is to provide a composite particle obtained by the above-mentioned method for preparing the core-shell structure copper oxide-carbon nitride nanotube composite particle.

[0014] A third object of the present invention is to provide the use of composite particles as a photocatalyst. Furthermore, the photocatalyst includes a catalyst for photocatalytic decomposition of water to produce hydrogen.

[0015] The advantages and beneficial effects of the present invention are: The preparation method of the core-shell structure copper oxide-carbon nitride nanotube composite particles uses carbon nitride nanotubes prepared by a water-induced phase change formation method as raw materials, loads soluble copper salts on the inner and outer surfaces of the carbon nitride nanotubes, and then calcines in a reducing atmosphere to partially reduce copper oxide to obtain cuprous oxide; the cuprous oxide-copper oxide nanoparticles have a moderate size and are evenly distributed and tightly combined with the inner and outer surfaces of the carbon nitride nanotubes; Cu 2 O is easily oxidized, while CuO is relatively stable. CuO can protect Cu as a shell. 2 O, the core-shell structure can adjust the electronic structure and improve the electrical properties of the material; the introduction of Cu 2 The O core can raise the energy band position of the core-shell nanoparticles, thus forming a Z-type energy band structure, accelerating charge carrier transfer and increasing photoreduction ability; The reducing atmosphere is different from adding the reducing agent at a predetermined rate, so that the morphology of the cuprous oxide-copper oxide modified carbon nitride nanotube core-shell structure is easier to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is an X-ray diffraction (XRD) pattern of the core-shell structure copper oxide-carbon nitride nanotube composite particles of Example 1; Figure 2 is a transmission electron microscope (TEM) image of the core-shell structure copper oxide-carbon nitride nanotube composite particles of Example 1; Figure 3 It is a comparison chart of the photocatalytic hydrogen production performance of the catalysts obtained in Examples 1-9. DETAILED DESCRIPTION

[0017] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.

[0018] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0019] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0020] Unless otherwise specified, the raw materials used in the examples were purchased commercially.

[0021] The carbon nitride nanotubes used in the embodiment are prepared by a water-induced phase change formation method. The diameter of the carbon nitride nanotubes is 100 nm and the length is 1 μm.

[0022] The photocatalytic hydrogen production rate test method of the carbon nitride particles obtained in the embodiment: A xenon lamp light source with a 420 nm filter, 40 mg of photocatalyst, 5 mL of triethanolamine, and 45 mL of deionized water were placed in the reactor.

[0023] Example 1

[0024] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 67.95 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C. 2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 400°C; (5) The time of step (4) is 2 h. The particles loaded on the surface of the carbon nitride nanotubes (CNNTs) in the obtained composite material are core-shell structure Cu 2 O-CuO nanoparticles, with a small amount of nanoparticles and a size of 20-80 nm, and a hydrogen production rate of 347 µmol g cat -1 h -1 .

[0025] Example 2

[0026] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 37.75 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C. 2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 400°C; (5) The time of step (4) was set to 2 h, and the CNNTs surface-loaded particles in the obtained composite material were core-shell structure Cu 2 O-CuO nanoparticles, but the amount of nanoparticles is small, the nanoparticle size is about 20 nm, and the hydrogen production rate of the composite particles is 69 µmol g cat -1 h -1 .

[0027] Example 3

[0028] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 52.85 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C. 2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 400°C; (5) The time of step (4) was set to 2 h, and the CNNTs surface-loaded particles in the obtained composite material were core-shell structure Cu 2 O-CuO nanoparticles, but the amount of nanoparticles is small, the nanoparticle size is about 60 nm, and the hydrogen production rate of the composite particles is 88 µmol g cat -1 h -1 .

[0029] Example 4

[0030] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 83.05 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C.2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 400°C; (5) The time of step (4) was set to 2 h, and the CNNTs surface-loaded particles in the obtained composite material were core-shell structure Cu 2 O-CuO nanoparticles with a size of about 120 nm and a hydrogen production rate of 212 µmol g cat -1 h -1 .

[0031] Example 5

[0032] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 83.05 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C. 2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 200°C; (5) The time of step (4) was changed to 2 h. There were no obvious nanoparticles on the composite surface, and the hydrogen production rate of the composite particles was 54 µmol g cat -1 h -1 .

[0033] Example 6

[0034] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 83.05 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C. 2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 300°C; (5) The time of step (4) was set to 2 h, and the CNNTs surface-loaded particles in the obtained composite material were core-shell structure Cu 2 O-CuO nanoparticles with a size of about 20 nm and a hydrogen production rate of 108 µmol g cat -1 h-1 .

[0035] Example 7

[0036] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 83.05 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C. 2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 500°C; (5) The time of step (4) was set to 2 h, and the CNNTs surface-loaded particles in the obtained composite material were core-shell structure Cu 2 O-CuO nanoparticles with a size of about 200 nm and a hydrogen production rate of 246 µmol g cat -1 h -1 .

[0037] Example 8

[0038] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 83.05 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C. 2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 400°C; (5) The time of step (4) was changed to 1 h. There were no obvious nanoparticles on the surface of CNNTs in the obtained composite material, and the hydrogen production rate of the composite particles was 44 µmol g cat -1 h -1 .

[0039] Example 9

[0040] (1) Add 200 mg of carbon nitride nanotubes into 50 mL of deionized water and stir evenly; (2) Add 83.05 mg of copper nitrate to the mixture obtained in step (1), stir for 12 h, and dry the mixture at 80 °C and grind it; (3) The mixture obtained in step (2) is heated to 400 °C.2 / Ar(5% H 2 ) Calcination in atmosphere; (4) The calcination temperature of step (3) is 400°C; (5) The time of step (4) was set to 3 h, and the CNNTs surface-loaded particles in the obtained composite material were core-shell structure Cu 2 O-CuO nanoparticles with a size of about 110 nm and a hydrogen production rate of 267 µmol g cat -1 h -1 .

[0041] Comparison of hydrogen production performance of the core-shell structure copper oxide-carbon nitride nanotube composite particles obtained in Examples 1-9 Figure 3 shown.

[0042] The morphology and Figure 3 The comparison of hydrogen production performance shows that the core-shell Cu 2 The hydrogen production rates of Examples 5 and 8 of O-CuO nanoparticles were the lowest, and the photocatalytic performance was poor; Compared with other examples except Example 5 and Example 8, the photocatalytic performance of the core-shell structured copper oxide-carbon nitride nanotube composite particles obtained in Example 1 and Example 9 is better, indicating that the mass ratio of carbon nitride to copper nitrate, calcination temperature and time will have a significant effect on the morphology of the carbon nitride nanotube composite particles and their photocatalytic performance.

[0043] Compared with the carbon nitride microrods obtained in Example 9, the core-shell structure Cu 2 O-CuO nanoparticles have smaller particle size, more active sites, and higher catalytic hydrogen production rate.

[0044] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles, characterized in that: The following steps are involved: S1: Preparation of carbon nitride nanotubes by water-induced phase transition formation; S2: dispersing a predetermined amount of carbon nitride nanotubes in deionized water and mixing to obtain a carbon nitride dispersion; S3: adding soluble copper salt to the carbon nitride dispersion, stirring and mixing, drying and grinding to obtain a mixed powder; S4: calcining the mixed powder in a reducing atmosphere, and grinding to obtain core-shell structured copper oxide-carbon nitride nanotube composite particles.

2. The method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to claim 1, characterized in that: The mass volume concentration of the carbon nitride nanotubes and deionized water is 1-9 mg / mL.

3. The method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to claim 1, characterized in that: The soluble copper salt is copper nitrate, and the mass ratio of the carbon nitride nanotubes to copper nitrate is (1.74-4.14):

1.

4. The method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to claim 1, characterized in that: The reducing atmosphere contains hydrogen and inert gas, and the volume percentage of hydrogen in the reducing atmosphere is 2% to 20%.

5. The method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to claim 1, characterized in that: The calcination temperature of the S4 is 390-440°C.

6. The method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to claim 1, characterized in that: The calcination time of S4 is 0.5 to 5 hours.

7. The method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to claim 1, characterized in that: The drying temperature in S3 is 65-90°C.

8. The method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to claim 1, characterized in that: The carbon nitride nanotube has a diameter of 80 to 110 nm and a length of 0.9 to 1.2 μm.

9. Composite particles, characterized in that The composite particles are prepared by the method for preparing core-shell structured copper oxide-carbon nitride nanotube composite particles according to any one of claims 1 to 9.

10. Use of the composite particles according to claim 9 as a photocatalyst, wherein the photocatalyst further comprises a catalyst for photocatalytic decomposition of water to produce hydrogen.

Citation Information

Patent Citations

  • Cuprous oxide / tubular graphite-like carbon nitride composite catalyst as well as preparation method and application thereof

    CN112774718A